Carbon paste electrode containing dispersed bismuth powder for pH measurements - Metelka, Radovan; Žeravík, Marek; Vytřas, Karel (Univerzita Pardubice, 2010)
The carbon paste electrode containing 17 % (w/w) of dispersed bismuth powder, despite its well-known performance in electroanalytical stripping methods, was also evaluated as a potential pH sensor. Potentiometric response to pH of solutions was ascertained under batch and flow conditions and compared to that of classical glass electrode. Continuous flow or flow injection modes of analysis together with buffers of different pH were employed to study the behavior of modified carbon paste electrode in thin layer cell. Proposed pH sensor exhibited linear, sub-Nernstian response of -41.2 mV per pH unit within the working range of pH 2 – 10 in mode of flow injection analysis. The longest response time registered to sudden change in hydrogen ion activity was 40 s. The sensor works de facto sequentially in two modes of operation, which is rather interesting feature described for an electrochemical sensor.
Keywords: carbon paste electrodes; bismuth powder; electrode modification; pH measurements; flow injection analysis